2019
DOI: 10.1097/j.pain.0000000000001629
|View full text |Cite
|
Sign up to set email alerts
|

Onset of action of naldemedine in the treatment of opioid-induced constipation in patients with chronic noncancer pain: results from 2 randomized, placebo-controlled, phase 3 trials

Abstract: Naldemedine improves opioid-induced constipation in a timely manner in patients using opioids for noncancer pain; most experienced spontaneous bowel movement within 24 hours of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Rauck et al [39], in a randomized, double-blind trial showed that oral formulation of methylnaltrexone is efficacious and well-tolerated for OIC. Naldemedine is a novel PAMORA recently approved for the treatment of OIC [40][41][42][43][44][45]. Spontaneous BM is achieved earlier with naldemedine (16.1 or 18.3 h) than with placebo (46.7 or 45.9 h, respectively) [41].…”
Section: Peripherally Acting μ-Opioid Receptor Antagonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rauck et al [39], in a randomized, double-blind trial showed that oral formulation of methylnaltrexone is efficacious and well-tolerated for OIC. Naldemedine is a novel PAMORA recently approved for the treatment of OIC [40][41][42][43][44][45]. Spontaneous BM is achieved earlier with naldemedine (16.1 or 18.3 h) than with placebo (46.7 or 45.9 h, respectively) [41].…”
Section: Peripherally Acting μ-Opioid Receptor Antagonistsmentioning
confidence: 99%
“…Naldemedine is a novel PAMORA recently approved for the treatment of OIC [40][41][42][43][44][45]. Spontaneous BM is achieved earlier with naldemedine (16.1 or 18.3 h) than with placebo (46.7 or 45.9 h, respectively) [41]. Song et al [43] in a meta-analysis have suggested that naldemedine can improve the number of patients achieving spontaneous BM and its frequency.…”
Section: Peripherally Acting μ-Opioid Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an exploratory analysis [32], the onset of action of naldemedine was evaluated in two phase 3, randomized, placebo-controlled trials [29]. Proportion of patients experiencing a SBM within 24 hours of treatment initiation, time from initial dose to first SBM and weekly SBM frequency were assessed.…”
Section: Studies In Non-cancer Patientsmentioning
confidence: 99%
“…Naldemedine had a timely onset of effect, and GI adverse events largely resolved within the first week. These findings should assist clinicians counseling patients with chronic noncancer pain on expectations when initiating naldemedine for OIC [32]. In COMPOSE-4, 193 eligible patients were randomly assigned to naldemedine (n = 97) or placebo (n = 96).…”
Section: Studies In Non-cancer Patientsmentioning
confidence: 99%